Una aproximación a la información para la empresa desde las organizaciones públicas y privadas de Extremadura - Muñoz Cañavate, Antonio (Revista General de Información y Documentación, 2005)
Information and knowledge are essential assets in business administration. Various organizations — both public and private— have been playing a very important role in this context, having become information providers for the companies in their environment. Quite diverse organizations, including the Central Administration, Regional Administrations, Chambers of Commerce, and business organizations, inter al., have set up information providing structures with the aim of strengthening companies’ decision processes. We here present the most important initiatives in this area that have been undertaken in Extremadura. In particular, we refer to the Regional Administration in the agrarian and industrial sectors (although in the agrarian sector this goes back to the 1950s with the Agricultural Extension Service), to the Chambers of Commerce, to various European centres set up in the Region, and to organizations that act in defence of the interests of entrepreneurs.
Keywords: Business information; Extremadura; Public Administrations; Chambers of Commerce; associations of entrepreneurs